The mediating and moderating effects of resilience between childhood trauma and geriatric depressive symptoms among Chinese community-dwelling older adults - Li, Shaojie; Yin, Yongtian; Cui, Guanghui; Zhang, Chi; Zhu, He; Yao, Yao (Frontiers in Public Health, 2023)
Objective This study aims to examine the association between childhood traumatic events (CTEs), childhood trauma severity, and depressive symptoms, as well as to examine the mediating and moderating roles of resilience in these associations. Methods We conducted a cross-sectional study of 1,091 community-dwelling older adults in Jinan, China. The trauma history questionnaire (THQ) was used to measure CTEs and childhood trauma severity. CTEs were defined as the number of traumatic events before the age of 18. We calculated childhood trauma severity by multiplying the number of CTEs by the participants’ self-perceived impact level of the events from the THQ. We then applied the 15-item Geriatric Depression Scale and 10-item Connor–Davidson Resilience Scale to assess participants’ depressive symptoms and resilience, respectively. Linear regression models were used to examine the associations, and structural equation modeling was used to examine the mediating and moderating roles of resilience. Results Childhood traumatic events, childhood trauma severity, and resilience were all associated with depressive symptoms in older adults. Resilience mediated the relationship between childhood trauma severity and depressive symptoms (β = 0.082, 95% CI = 0.045–0.123), accounting for 26.6% of the overall effect (β = 0.308, 95% CI = 0.190–0.422). However, there was no evidence that resilience mediated the association between CTEs and depressive symptoms. In addition, we did not find that resilience played a moderating role in the associations of CTEs, childhood trauma severity with depressive symptoms. Conclusion Resilience plays a mediating role in the relationship between childhood trauma severity and depressive symptoms. Intervention measures on improving resilience may reduce childhood trauma severity associated with depression risk in older Chinese adults.